Financing SDG2 and ending hunger - Díaz-Bonilla, Eugenio (Springer, 2023)
This chapter focuses on innovation in mechanisms to finance the transformation of food systems to end hunger by 2030 and achieve SDG2. The key questions analyzed are: given the estimated costs involved in the transformation of food systems to achieve zero hunger, (1) What are the financing options available? (2) What is their quantitative availability? and (3) How to mobilize/reallocate the potential sources of finance? The concepts proposed here include international development finance, public budgets, banking, and capital markets at the global and national levels.